2007
DOI: 10.1038/sj.bjc.6603968
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of secreted frizzled-related protein 2 (SFRP2) by promoter methylation in human gastric cancer

Abstract: The role of secreted frizzled-related protein (SFRP) genes in gastric cancer remains largely unknown. We determined the frequency and functional significance of SFRPs hypermethylation in human gastric cancer. The expression and methylation status of four SFRP members (SFRP1, 2, 4, and 5) in primary gastric cancer samples was screened. The biological effects of SFRP were analysed by flow cytometry, cell viability assay and in vivo tumour growth in nude mice. Among the four SFRPs, only SFRP2 was significantly do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 24 publications
5
115
0
Order By: Relevance
“…These findings are consistent with those from other studies, which also reported a similar inverse correlation between the above proteins in endometrial, ovarian and breast cancer (37,38). The present findings, together with those from previous studies, suggest that sFRP2 may act as a tumor suppressor through its interaction with the Wnt canonical signaling pathway by modulating the cellular cytosolic pool of β-catenin (22).…”
Section: E D C B Asupporting
confidence: 93%
“…These findings are consistent with those from other studies, which also reported a similar inverse correlation between the above proteins in endometrial, ovarian and breast cancer (37,38). The present findings, together with those from previous studies, suggest that sFRP2 may act as a tumor suppressor through its interaction with the Wnt canonical signaling pathway by modulating the cellular cytosolic pool of β-catenin (22).…”
Section: E D C B Asupporting
confidence: 93%
“…Over the past several years, many TSGs have been found to be epigenetically inactivated in gastric cancer, indicating that epigenetic silencing of TSGs is one of the major molecular alterations in the process of gastric carcinogenesis To et al, 2002;Choi and Wu, 2005;Chan and Rashid, 2006;Sato and Meltzer, 2006;Cheng et al, 2007). In this study, FBLN1 was identified as another candidate TSG whose inactivation may contribute to gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…Genomic DNA was bisulphite-treated with the Zymo DNA Modification Kit (Zymo Research, Orange, CA, USA) according to the protocol provided. Methylation-specific PCR was carried out for 40 cycles with annealing temperature at 621C, as described earlier (Cheng et al, 2007). Methylation-specific primers were FBLN1M-F: 5 0 -attaggagattcgcggtttc and FBLN1M-R: 5 0 -gctccataaacgacgaacg, and the unmethylation-specific primers were FBLN1U-F: 5 0 -gattaggagatttgtggttttg and FBLN1U-R: 5 0 -cacactccataaacaacaaaca.…”
Section: Rt -Pcr and Quantitative Real-time Rt -Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…e bisul temodi ed DNA was subjected to methylation-speci c polymerase chain reaction (MS-PCR) for detection of the methylation status of the CpG-rich region (-219 to -81 relative to the transcription start site) in the SFRP2 promoter, as described previously [27].…”
Section: Methodsmentioning
confidence: 99%